The spokesman of polyphony: considerations on the socio-aesthetic analysis of modern ethnic art, with a view at the baiano field - Armstrong, Piers (2016)
In this essay the pragmatic use of the notion of ethnicity is investigated according to specific contextual connotations and socio-political insertions. The most current uses of "ethnicity" in Brazil and in the US are compared. Such uses are analyzed in relation to the cultural policy of the Lula government and to the development of African studies. One argues, here, that as the Minister of Culture Gilberto Gil plays a central symbolic role in the relation between these two fields. The socio-aesthetic philosophy of the Tropicalismo still lingers in the national context, while the cultural heritage from Bahia has become a national reference. The debate on Affirmative Action and other related academic trends suggest a North-American influence, which holds an underlying ethnic notion that is distant from the Tropicalismo. It is argued that ethnic expression and cultural competence are largely autonomous in relation to the criteria evoked in the political debate. Communitarian art is an alliance of interests and interested ones, in which the aesthetic, the moral and the objective combine.